2007
DOI: 10.1104/pp.107.103465
|View full text |Cite
|
Sign up to set email alerts
|

A Predicted Interactome for Arabidopsis

Abstract: The complex cellular functions of an organism frequently rely on physical interactions between proteins. A map of all proteinprotein interactions, an interactome, is thus an invaluable tool. We present an interactome for Arabidopsis (Arabidopsis thaliana) predicted from interacting orthologs in yeast (Saccharomyces cerevisiae), nematode worm (Caenorhabditis elegans), fruitfly (Drosophila melanogaster), and human (Homo sapiens). As an internal quality control, a confidence value was generated based on the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
314
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(323 citation statements)
references
References 44 publications
7
314
1
1
Order By: Relevance
“…openfoundry.org/) based on the Interactome 2.0 (Geisler- Lee et al, 2007) downloaded from The Arabidopsis Information Resource database (ftp://ftp. arabidopsis.org/home/tair/Proteins/Interactome2.0/).…”
Section: Protein Fishing Based On Protein-protein Interactionsmentioning
confidence: 99%
“…openfoundry.org/) based on the Interactome 2.0 (Geisler- Lee et al, 2007) downloaded from The Arabidopsis Information Resource database (ftp://ftp. arabidopsis.org/home/tair/Proteins/Interactome2.0/).…”
Section: Protein Fishing Based On Protein-protein Interactionsmentioning
confidence: 99%
“…Although there have been several PPI studies in Arabidopsis, their main focus lay in building the interactome rather than on breaking down the network to the module level (Fujikawa and Kato, 2007;Geisler-Lee et al, 2007;Van Leene et al, 2007;Arabidopsis Interactome Mapping Consortium, 2011;Li et al, 2011). Studies that did explore the network module contexts found modules recapitulating known biological functions and also suggesting new biological hypotheses for several plant-specific genes, often through the integration with expression data (De Bodt et al, 2009Boruc et al, 2010;Arabidopsis Interactome Mapping Consortium, 2011).…”
mentioning
confidence: 99%
“…Furthermore, PIN is an effective tool for understanding the complex world of biological processes inside the cell and solving various biological problems in signal transduction, gene regulation, and metabolism. [9] Given the significant importance of PINs, proteome-wide interaction networks have been studied in many organisms from prokaryote [10] to eukaryote [11], from unicellular [12] to human [13]. The technique of collecting protein interaction datasets for reconstructing a PIN is improving and the applications of PINs have spread into more to be more closely determined by their interactions than by the characteristics of their individual components.…”
Section: Introductionmentioning
confidence: 99%